Relationship Between Patterns of Complementary Feeding (MPASI) and Nutritional Status of Toddlers Aged 6-24 Months - Luh Mertasari; Yulia Paramita Rusady; Tutus Anggi Prihartanti; Titis Budi Rahayu; Santi Aprilian Lestaluhu (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Nutritional problems among toddlers aged 6–24 months remain a significant challenge in achieving optimal child growth and development. Complementary feeding (MPASI) is one of the key factors influencing the nutritional status of toddlers. This study aimed to analyze the relationship between complementary feeding patterns and the nutritional status of toddlers aged 6–24 months in the working area of Tarok Health Center, Payakumbuh. This study employed an analytic observational design with a cross-sectional approach. A total of 95 toddlers who met the inclusion criteria were selected through purposive sampling. Data on complementary feeding patterns were collected using a structured questionnaire, while nutritional status was assessed through anthropometric measurements based on World Health Organization (WHO) standards. Data were analyzed using univariate analysis to describe feeding patterns and nutritional status and bivariate analysis using the chi-square test and Odds Ratio (OR). The results showed that 68% of toddlers received complementary feeding according to recommendations, while 32% did not. Regarding nutritional status, 70% had normal nutritional status, 20% were undernourished, and 10% were overnourished. Bivariate analysis revealed a significant relationship between complementary feeding patterns and nutritional status (χ² = 15.23; p = 0.0001). Toddlers who received inappropriate complementary feeding were 3.5 times more likely to experience malnutrition. These findings highlight the importance of proper complementary feeding practices in improving toddler nutritional status.